Analisis Faktor Sosiodemografi Kejadian Persalinan Preterm di RSUP Dr. Mohammad Hoesin Palembang Tahun 2019 - Dwi Kuslimawati; Fika Minata Wathan; Helni Anggraini (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Preterm labor is delivery that occurs less than 37 weeks or 259 days after gestation or birth weight of the fetus of less than 2,500 grams. Sociodemographic factors influence the implementation of preterm labor. This study aims to determine the relationship between sociodemographic factors including age, occupation, education, maternal smoking and alcohol habits on the incidence of preterm labor at Dr. Mohammad Hoesin Central Hospital Palembang in 2019. This research is a quantitative study using a cross sectional design with a sample size of 317 respondents with a systematic random sampling technique. Data collection was done by viewing and recording maternal data in medical records, on variables of maternal age, maternal occupation, smoking habits, drinking alcohol habits and preterm labor using a checklist designed by the researcher. This research was conducted at Dr. Mohammad Hoesin Central Hospital Palembang from July to August 2020. Data were analyzed using the chi square test. The results of the analysis showed that there was a relationship between maternal occupation and the incidence of preterm labor (p value = 0.045 <0.05) with an OR value of 0.528, meaning that working mothers had a 0.528 times more risk of experiencing preterm labor than non-working mothers. Simple logistic regression analysis concluded that working mothers had a risk of experiencing preterm labor by 63,94%. Of the five sociodemographic factors measured in this study, maternal occupational factors have a relationship between incidence of preterm labor. These results can be used as a basis for information on promotional measures and to prevent the incidence of preterm labor.